(untitled) (Research, Society and Development, 2020)
Yogurt is a product resulting from the action of lactic bacteria on milk during fermentation. The present study aimed to monitor the kinetic parameters of the fermentation of milk added with Banana Green Flour for the production of yogurt. This is a quantitative study, in which the fermentation process of milk with or without the addition of flour was evaluated for 24 hours with respect to dry weight, reducing sugars and acidity in lactic acid. After this period, it can be seen that the exponential growth of the lactic culture occurred in the initial 6 hours, at which time the parameters of Product formation rate, Yield in lactic acid, Consumption of substrate and Speed of cell growth were estimated. At the end it can be concluded that despite the Banana Green Flour is not a stimulating factor for the growth of lactic acid bacteria, because the speed of cell growth was reduced by half, in parallel this ingredient stimulated the formation of lactic acid which is the product of interest in the development of yogurt. Therefore, it is recommended to use it in the production of yogurt.